2014
DOI: 10.4103/1008-682x.122875
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer metastasis-driving genes: hurdles and potential approaches in their identification

Abstract: Metastatic prostate cancer is currently incurable. Metastasis is thought to result from changes in the expression of specific metastasis-driving genes in nonmetastatic prostate cancer tissue, leading to a cascade of activated downstream genes that set the metastatic process in motion. Such genes could potentially serve as effective therapeutic targets for improved management of the disease. They could be identified by comparative analysis of gene expression profiles of patient-derived metastatic and nonmetasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…HOXC6 is involved in epithelial cell proliferation, and loss of this gene induces apoptosis in prostate cancer cells [30, 31]. DLX1 encodes a distal-less homeobox 1 protein that is reported to drive prostate cancer metastasis [32]. Upon independent knockdown of these genes in C42B prostate cancer cells, we found that for HOXC6, the top GO terms for downregulated genes were mitotic cell cycle and cell cycle (e.g., CDKN2C , CDK16 , IGFBP3 ), and for DLX1, genes involved in proliferation and androgen-responsive genes were enriched in downregulated genes (e.g., CDCA7 , MAGOH , MAD2L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…HOXC6 is involved in epithelial cell proliferation, and loss of this gene induces apoptosis in prostate cancer cells [30, 31]. DLX1 encodes a distal-less homeobox 1 protein that is reported to drive prostate cancer metastasis [32]. Upon independent knockdown of these genes in C42B prostate cancer cells, we found that for HOXC6, the top GO terms for downregulated genes were mitotic cell cycle and cell cycle (e.g., CDKN2C , CDK16 , IGFBP3 ), and for DLX1, genes involved in proliferation and androgen-responsive genes were enriched in downregulated genes (e.g., CDCA7 , MAGOH , MAD2L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of TIM in hepatocellular carcinoma cells induces apoptosis, arrests cell cycle in the G2 phase, and inhibits cell migration by perturbing the interaction with eukaryotic elongation factor 1A2 (EEF1A2) [ 11 ]. Moreover, TIM is upregulated in tissue in metastatic prostate cancer, and TIM knockdown in prostate cancer cell PC3M suppresses cell migration [ 13 ]. More recently, alteration of TIM expression in breast cancer has been reported to be associated with advanced tumor stage and poorer prognosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports show the involvement of TIM in human cancers [19] of many different organs, including lung [20], breast [21][22][23], liver [24], prostate [25], colon [26], kidney [27], bladder [28], pancreas [29], and blood [30]. Sjoblom et al [31] showed that TIM mutations are involved in breast cancer.…”
Section: Research Paper Wwwoncotargetcommentioning
confidence: 99%